The effect of omega-3 supplementation on metabolic, inflammatory and oxidative stress biomarkers in pregnant women: a systematic review and meta-analysis - Saadh, Mohamed J.; Sabah Ghnim, Zahraa; Salih Mahdi, Morug; Baldaniya, Lalji; Karim, Sairah Abdul; Srivastava, Manish; Bhanot, Deepak; Rizaev, Jasur; Taher, Waam Mohammed; Alwan, Mariem; Jawad, Mahmood Jasem; Hamad, Atheer Khdyair (Frontiers in Nutrition, 2025)
BackgroundThis meta-analysis evaluates the effects of omega-3 supplementation on metabolic, inflammatory, and oxidative stress in pregnancy women by synthesizing findings from randomized controlled trials (RCTs), as existing evidence remains inconclusive.MethodsA systematic search was conducted using PubMed, Scopus, and Web of Science until July 2024. Random-effects models were applied to estimate each outcome's standardized mean difference (SMD) and 95% confidence intervals (CI).ResultsA total of 14 studies were included in the meta-analysis. The duration of omega-3 supplementation ranged from 6 to 29 weeks. Omega-3 supplementation did not have a significant effect on FBS (SMD = −0.74, 95% CI: −1.94, 0.45), and insulin (SMD = −0.76, 95% CI: −1.77, 0.24), TC (SMD = 0.11, 95% CI: −0.20, 0.42), and LDL-C (SMD = 0.32, 95% CI: −0.17, 0.81), IL-6 (SMD = 2.12, 95% CI: −0.56, 4.80), MDA (SMD = −1.67, 95% CI: −3.39, 0.05), and TAC (SMD = 2.59, 95% CI: −0.37, 5.54). However, triglyceride (SMD = −0.96, 95% CI: −1.77, −0.16) and CRP (SMD = −0.98, 95% CI: −1.86, −0.11) significantly decreased, and HDL-C cholesterol levels significantly increased (SMD = 0.72, 95% CI: 0.21, 1.22) following omega-3 supplementation.ConclusionThis study suggests omega-3 supplementation may improve lipid profiles and reduce inflammatory biomarkers during pregnancy. However, the presence of heterogeneity across trials highlights the need for further well-conducted studies. Thus, findings should be interpreted with caution.